High lipid accumulating bacteria isolated from dairy effluent scum grown on dairy wastewater as potential biodiesel feedstock. (15th December 2019) - Behera, Ashis Ranjan; Dutta, Kasturi; Verma, Priyanka; Daverey, Achlesh; Sahoo, Deepak Kumar
Abstract: The study evaluated the lipid accumulation potential of bacteria isolated from dairy effluent scum by the valorization of dairy wastewater as a renewable feedstock for biodiesel production. Three oleaginous bacteria ( i.e. DS-1, DS-6, and DS-7) were screened on the basis of their lipid accumulation (>20% lipid content) and productivity on a glucose-based medium. The effect of different carbon sources ( i.e. lactose, sucrose, starch, glucose, and xylose) on lipid accumulation capacity of the bacterial isolates was evaluated. The rod-shaped oleaginous bacterium DS-7 could accumulate 90% lipid with 1.2 g/l·d lipid productivity using lactose as a sole source of carbon. The bacteria could efficiently utilize dairy wastewater ( 50% reduction in BOD) with reasonably high lipid accumulation (72.78%), biomass production (4.29 g/l) and lipid productivity (0.727 g/l·d). The lipids accumulated by bacterium DS-7 were mostly neutral lipids and contained fatty acids of chain length C14:0-C18:0, as confirmed by nile red staining and nuclear magnetic resonance (NMR) spectroscopy. Fourier-transform infrared (FTIR) spectroscopy and gas chromatography (GC) analysis of fatty acid methyl esters (FAME) revealed that transesterified bacterial lipids from the isolated bacteria DS-7 are suitable for biodiesel applications. Graphical abstract: Image 1 Highlights: High lipid accumulating bacteria (DS-7) were isolated from dairy effluent scum. Isolated bacteria DS-7 could accumulate 90% lipid using lactose as carbon. DS-7 utilized dairy wastewater and accumulated 72.78% lipid. Accumulated neutral lipids are suitable for biodiesel production.